2013
DOI: 10.1371/journal.pone.0064753
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flavin-Based Fluorescent Proteins: An Emerging Class of Fluorescent Reporters

Abstract: Fluorescent reporter proteins based on flavin-binding photosensors were recently developed as a new class of genetically encoded probes characterized by small size and oxygen-independent maturation of fluorescence. Flavin-based fluorescent proteins (FbFPs) address two major limitations associated with existing fluorescent reporters derived from the green fluorescent protein (GFP)–namely, the overall large size and oxygen-dependent maturation of fluorescence of GFP. However, FbFPs are at a nascent stage of deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
130
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 61 publications
10
130
0
2
Order By: Relevance
“…The requirement for FMN does not restrict its utility as a fluorescent reporter, as this appears to be in plentiful supply in bacterial, plant and human cells [16 ] nor limit their targeting to subcellular compartments [16 ,17]. Moreover, the fast maturation of LOV fluorescence (with minutes) constitutes one advantage over GFP as a noninvasive real-time reporter of transcriptional activities [18]. However, it is worth noting that LOV-based FPs engineered thus far exhibit fluorescence quantum yields (Q F ) that are significantly lower (0.2-0.4; Table 1) to that of GFP (0.6) [2], which could impact their utility for certain reporter applications.…”
Section: Lov-domain Function and Fluorescencementioning
confidence: 99%
“…The requirement for FMN does not restrict its utility as a fluorescent reporter, as this appears to be in plentiful supply in bacterial, plant and human cells [16 ] nor limit their targeting to subcellular compartments [16 ,17]. Moreover, the fast maturation of LOV fluorescence (with minutes) constitutes one advantage over GFP as a noninvasive real-time reporter of transcriptional activities [18]. However, it is worth noting that LOV-based FPs engineered thus far exhibit fluorescence quantum yields (Q F ) that are significantly lower (0.2-0.4; Table 1) to that of GFP (0.6) [2], which could impact their utility for certain reporter applications.…”
Section: Lov-domain Function and Fluorescencementioning
confidence: 99%
“…These cyan-green fluorescing proteins bind flavin mononucleotide (FMN) as the chromophore and are either derived from bacterial photoreceptors (FMN-binding fluorescent proteins; FbFP 8 ) or are derivatives of the Arabidopsis thaliana phototropin 2 LOV2 domain (iLOV, miniSOG; 9,12 ). In contrast to all members of the GFP family, this novel class of LOV-based FPs develops the corresponding fluorescence signal under both, aerobic and anaerobic conditions 8,13,14 . This unique property renders them valuable for in vivo applications where molecular oxygen is limited; such as the analysis of microbial pathogenesis, hypoxia induced inflammatory processes, tumor pathophysiology and microbial fermentation as well as for the monitoring and optimization of bioremediation and bacterial production processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of iLOV as alternative fluorescent tag enabled advanced studies of the localization, movement and dynamics of target proteins and viruses 9,10,31,32 . Furthermore, in vivo and in vitro studies demonstrated that, in contrast to GFP-like proteins, LOV-based reporter proteins rapidly gain their fluorescence-active conformation because of their fast folding kinetics and the spontaneous incorporation of the chromophore 14,33 , thereby enabling their application as real-time reporters. Their rapid assembly as well as the robustness of the fluorescence signal have rendered LOV-based FPs valuable quantitative reporters for biotechnological approaches [33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, we have observed that overexpression of FbFPs may lead to varying degrees of metabolic burden and a concomitant reduction in cellular growth rate [38]. Based on these results, we conjecture that targeted mutagenesis of FMN-binding pocket amino acids or 'insoluble' hydrophobic patches in FbFPs could be particularly useful for optimizing FbFPs for improved intracellular expression and brighter fluorescence.…”
Section: Key Challenges and Future Directionsmentioning
confidence: 92%
“…In a recent and impressive study, Wingen et al addressed this issue by developing a robust platform for precise characterization and comparison of key spectral properties of existing FbFPs [37]. Similarly, in our lab, we have tackled this challenge by comprehensively characterizing biophysical and biochemical properties of FbFPs [38], in tandem with developing new FbFP variants using protein engineering. Strikingly, our results suggest that FbFPs (in particular iLOV and CreiLOV) exhibit multiple advantages as fluorescent reporter probes, including an overall 20 Analytical biotechnology ( Figure 2 Legend Continued) as miniSOG expressed in the mitochondria as a cytochrome C fusion and imaged via fluorescent microscopy.…”
Section: Key Challenges and Future Directionsmentioning
confidence: 97%